Public Policy and the Dynamics of Children's Health Insurance, 1986–1999 - Ham, John C; Li, Xianghong; Shore-Sheppard, Lara D (American Economic Review, 2009)
The past 20 years have seen important changes in public policy with the potential for significant impacts on health insurance for children. These changes included both those explicitly intended to expand access to public insurance for children, including expansions in eligibility for Medicaid and the introduction of the State Children’s Health Insurance Program (SCHIP), and other changes in antipoverty policy. Since health insurance coverage among children is entwined with parental welfare participation and employment, shifts in policy designed to encourage work in place of welfare participation–such as welfare reform and the expansion of the Earned Income Tax Credit (EITC)–may have secondary impacts on children's health insurance coverage. As parents leave welfare, with its guaranteed health insurance through Medicaid, for jobs that may or may not have health insurance coverage offered as a benefit, children may experience a change in the source of their health insurance coverage or may become uninsured. Similarly, changes in health care markets and economic conditions such as rising health care prices and cyclicality in the availability of employment may also affect children's coverage. Despite the potential importance of these factors for coverage, the fraction of children who are uninsured has remained largely constant, particularly through the 1990s. However, this relatively constant level of uninsurance may mask changes in the underlying dynamics of health insurance among children. In this paper, we use monthly data from the 1986–1996 panels of the Survey of Income and Program Participation (SIPP) to examine patterns of health insurance coverage among children during the period 1986–1999, focusing on transitions between public coverage, private coverage, and no coverage. Using these data, we find that over the 1990s the rate of transitions among all three insurance states–public insurance, private insurance, and no insurance–increased, with a particular increase in transitions involving public coverage. We investigate whether there is evidence of a relationship between insurance transitions and various policy and economic variables, focusing on the impacts of expansions in public coverage availability, the effects of other policies directed at the poor that affect employment and insurance coverage, and economic conditions. We find that several of the policy changes that took place over the 1990s had important effects on health insurance transitions for children.